Do women perform fellatio as a mate retention behavior?. (January 2015) - Sela, Yael; Shackelford, Todd K.; Pham, Michael N.; Euler, Harald A.
Highlights: Women who perform more partner-directed oral sex also perform more mate retention. Replicates relationships found for men's partner-directed oral sex and mate retention. Both sexes perform oral sex as part of a benefit-provisioning mate retention strategy. Abstract: Men who report performing more mate retention behaviors, in general, and more benefit-provisioning mate retention behaviors, in particular, also report greater interest in, and spend more time, performing oral sex on their female partner. We extended these findings to a female sample to investigate whether women's oral sex behaviors are related to their mate retention behaviors. We secured self-report data from 410 women residing in the United States or in Germany in a committed, sexual, heterosexual relationship. The results indicate that women who report performing more benefit-provisioning mate retention behaviors also report greater interest in, and spend more time, performing oral sex on their partner. Further, there are no sex differences in the magnitudes or directions of these relationships. The results suggest that both men and women are more interested in, and spend more time, performing oral sex on their partner as part of a benefit-provisioning strategy to increase their partner's relationship satisfaction. We address limitations of this research, and discuss explanations for the results.